Educational Policy and the Inclusive Turn: A Comparative Study of Special Education Reform in Latin America - Artero Abellan, Pablo Agustin (Exceptionality Education International, 2026)
In this article, I examine the evolution of special education policy in Latin America through the lens of inclusive education, analyzing how global discourses on equity and disability rights have been translated into national reforms. I compare four countries—Argentina, Brazil, Mexico, and Chile—to identify both shared trends and divergent approaches in the region’s pursuit of inclusion. Using qualitative comparative policy analysis, I reviewed official legislation, government reports, and strategic frameworks across the selected cases. Countries were chosen for their geographic and political diversity, as well as for their documented engagement with inclusive education over the past two decades. Findings revealed a broad regional shift toward inclusive models, with formal commitments to the social model of disability and global frameworks such as the United Nations Convention on the Rights of Persons with Disabilities. However, substantial variation existed in implementation, particularly in funding, teacher preparation, and intersectoral coordination. Argentina and Brazil displayed more cohesive national strategies, while Mexico and Chile exhibited hybrid models with systemic tensions. The article underscores the role of educational leadership in bridging policy and practice, highlighting the need for sustained investment, cultural change, and capacity-building to turn inclusive ideals into educational realities in resource-constrained settings.